PENINGKATAN MUTU PEMBELAJARAN MEMBACA DAN MENULIS PERMULAAN SEBAGAI UPAYA PENINGKATAN LITERASI DI SD NEGERI INPRES PERUMNAS I WAENA JAYAPURA - Supardi Supardi; Yacobus Paidi (LPPM Uncen, 2018)
The activities of this community service were gaven training to the teachers at SDN Inpres Perumnas I Waena. The aimed of this training were to provide the teachers with the ability to : 1) understand MMP methode; 2) create a curriculum based on local knowledge; 3) innovate variety of learning media; 4) construct evaluation tools; 5) construct RPP and 5) conduct real teaching. CBSA method with complex approach such as lecturer, questions and answer session, task response, discussion and teaching, practice has been used on this training. The trainers were very enthustiastic and recognized their weakness in conducting MMP method during the class.Keywords: Jayapura, Literasi, MMP Methode, Profesionalisme guru